2016
DOI: 10.1111/jopr.12409
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Simulated Aging of Silicone Maxillofacial Elastomers: Advancements in the Past 45 Years

Abstract: It is imperative to overcome the existing variability by establishing unified national or international standards/specifications for maxillofacial prosthetic materials. Standardization organizations or bodies, the scientific community, and academia need to be coordinated to achieve this goal. In the meantime and despite all of these theoretically significant alternatives, clinical practice still faces problems with serviceability of maxillofacial prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 79 publications
(159 reference statements)
0
23
0
2
Order By: Relevance
“…In addition to these, two articles that evaluated the effect of accelerated aging on the physical properties of MDX‐4‐4210 were included. The tensile strength properties of all the mechanical properties were selected for the meta‐analysis, as this property is most crucial for the clinical serviceability of the prostheses …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these, two articles that evaluated the effect of accelerated aging on the physical properties of MDX‐4‐4210 were included. The tensile strength properties of all the mechanical properties were selected for the meta‐analysis, as this property is most crucial for the clinical serviceability of the prostheses …”
Section: Discussionmentioning
confidence: 99%
“…The tensile strength properties of all the mechanical properties were selected for the meta-analysis, as this property is most crucial for the clinical serviceability of the prostheses. 45 Figure 4 shows the results for the meta-analysis comparing the effect of outdoor weathering and natural/artificial/ accelerated aging on the tensile strength properties of specific maxillofacial silicone elastomers (MDX-4-4210, A-2186, Techsil S25). The meta-analysis of the five studies together favored the case group, with an effect size of 0.497, 95% confidence interval (CI) between 0.231 and 1.073 (i.e., tensile strength properties of case groups of the abovementioned facial silicone elastomers were affected by outdoor weathering and accelerated aging).…”
Section: Meta-analysis Of Effect Of Aging Condition On Mechanical Promentioning
confidence: 99%
“…Therefore, artificial aging under simulated conditions is an essential part of an in vitro study that tests prosthetic materials' clinical performances. Light's effects on the aging properties of maxillofacial silicone elastomers have been widely studied, and these studies revealed that sun-associated ultraviolet radiation negatively affects the color stability and ideal physical properties of maxillofacial silicones [33][34][35] . With regard to bond strength between silicone and acrylic resin substructure, studies have revealed that both light and heat cause an increase in aging due to further silicone photo-polymerization and reactions with pendant C=C bonds from reactive free radicals of resin material 36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the principal material of preference has been silicone elastomers [57][58][59][60] Margin deterioration of the prostheses occurs due to cosmetics, adhesives, strong solvents or cleansers used alongside the prostheses causing it to degrade; losing the fine thin edges that seamlessly blends with the anatomic human skin and the extrinsic colouring [51]. Most current materials have a low tear strength and poor wettability [68].…”
Section: Lack Of "Ideal" Materialsmentioning
confidence: 99%